Os idosos no serviço de atenção primária à saúde: contribuições para a gestão de uma unidade no SUS - Gomes, Márcia Constância Pinto Aderne (2017)
This is a qualitative research with descriptive and propositional character, since it sought to know and report the daily health practices of a primary health care unit of SUS concerning the relation of supply and demand for care for elderly patients. Thus, the case study was chosen as a methodological strategy to understand the concepts related to aging, demand and supply of health services, organization of care, infrastructure, work process, health care evaluation of the elderly and production of care as actually happened in practice. Different types of data were collected: interviews with the elderly, relatives, health professionals; documentary information; data in medical records and in production unit monitoring systems; notes on direct observation and participant observation, and physical artifacts completed the set of evidence that was selected and presented in the form of a report. In this, the qualitative data of verbal nature were organized and tabulated, presented in the form of Discourse of the Collective Subject. Aging occurs procedurally, is not homogeneous and should be understood as part of a natural process of diminishing the functional reserve of the individual – senescence – or may be accompanied by conditions requiring assistance – senility. Care and care should then be organized in order to attend to both senescence and senility. Living with and accompanying the elderly in their health needs brings several challenges, among which is the care at the end of life. Once the problems / challenges that hinder access and care for the elderly have been understood, a set of strategies / proposals is presented to overcome the adverse conditions in the search for care for the elderly.